Method of manufacturing polarizing film

JP2023166878A5Pending Publication Date: 2025-01-10NITTO DENKO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022077712
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-05-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Polarizing films in image display devices can affect display characteristics due to issues like streaks, which are visible on the screen, particularly in displays with highly reflective metal layers such as OLEDs and QLEDs.

Method used

A method for manufacturing a polarizing film involves contacting a resin film containing iodine with a first liquid, typically an aqueous boric acid solution at elevated temperatures, followed by additional processing steps to achieve a high stretching ratio and controlled orientation, resulting in a film with reduced streaks and improved appearance.

Benefits of technology

The method produces a polarizing film with enhanced appearance and display characteristics by minimizing streaks and optimizing optical properties, suitable for use in various image display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a polarizing film which has superior appearance and may contribute to improvement in display characteristics of image display devices.SOLUTION: A method of manufacturing a polarizing film according to an embodiment of the present invention comprises bringing a resin film containing iodine and having a moisture content of 15 wt.% or less into contact with a first liquid. The first liquid is an aqueous solution of boric acid and iodide and is kept at a temperature of 60°C or higher.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to a method for manufacturing a polarizing film. [Background technology]

[0002] Liquid crystal displays, a typical image display device, have polarizing films positioned on both sides of the liquid crystal cell due to their image formation method. Furthermore, with the spread of thin-screen displays, displays equipped with organic electroluminescent (EL) panels (OLEDs) and displays using display panels made of inorganic light-emitting materials such as quantum dots (QLEDs) have been proposed. These panels have a highly reflective metal layer, which can easily cause problems such as reflection of ambient light and reflection of the background. Therefore, it is known that these problems can be prevented by providing a circular polarizer having a polarizing film and a λ / 4 plate on the viewing side (for example, Patent Documents 1 and 2). [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication No. 2002-372622 [Patent Document 2] Patent No. 3325560 [Overview of the project] [Problems that the invention aims to solve]

[0004] As described above, when a polarizing film is installed in an image display device, the appearance of the polarizing film may affect the display characteristics of the image display device. For example, if streaks appear on the polarizing film, these streaks may be visible on the image display device.

[0005] The present invention was made to solve the above problems, and its main objective is to provide a polarizing film that has excellent appearance and can contribute to improving the display characteristics of an image display device. [Means for solving the problem]

[0006] 1. A method for producing a polarizing film according to an embodiment of the present invention comprises contacting a resin film containing iodine and with a moisture content of 15% by weight or less with a first liquid, wherein the first liquid is an aqueous solution of boric acid and iodide, and the temperature of the first liquid is 60°C or higher. 2. In the manufacturing method described in item 1 above, the permeability of the resin film that comes into contact with the first liquid may be 44% or more. 3. In the manufacturing method described in 1 or 2 above, the boric acid concentration of the first liquid may be 4% by weight or more. 4. In the manufacturing method described in any of items 1 to 3 above, the iodide concentration of the first liquid may be 2% by weight to 10% by weight. 5. The manufacturing method described in any of items 1 to 4 above may include bringing the resin film that has been in contact with the first liquid into contact with the second liquid. 6. In the manufacturing method described in item 5 above, the second liquid may contain water. 7. In the manufacturing method described in any of items 1 to 6 above, a polarizing film with a thickness of 8 μm or less may be obtained. [Effects of the Invention]

[0007] According to the present invention, a polarizing film with excellent appearance can be obtained. [Brief explanation of the drawing]

[0008] [Figure 1] This is a schematic cross-sectional view showing the general structure of a laminate according to one embodiment of the present invention. [Figure 2] This is a schematic diagram showing an example of drying using a heated roller. [Figure 3] This is a schematic cross-sectional view showing the general configuration of a polarizing plate according to one embodiment of the present invention. [Modes for carrying out the invention]

[0009] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.

[0010] (Definitions of Terms and Symbols) The definitions of the terms and symbols in this specification are as follows. (1) Refractive Index (nx, ny, nz) "nx" is the refractive index in the direction where the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction orthogonal to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-Plane Phase Difference (Re) "Re(λ)" is the in-plane phase difference measured with light of wavelength λ nm at 23°C. For example, "Re(550)" is the in-plane phase difference measured with light of wavelength 550 nm at 23°C. Re(λ) is obtained by the formula: Re(λ) = (nx - ny) × d, where d (nm) is the thickness of the layer (film). (3) Phase Difference in the Thickness Direction (Rth) "Rth(λ)" is the phase difference in the thickness direction measured with light of wavelength λ nm at 23°C. For example, "Rth(550)" is the phase difference in the thickness direction measured with light of wavelength 550 nm at 23°C. Rth(λ) is obtained by the formula: Rth(λ) = (nx - nz) × d, where d (nm) is the thickness of the layer (film). (4) Nz Coefficient The Nz coefficient is obtained by Nz = Rth / Re. (5) Angle When referring to an angle in this specification, the angle includes both clockwise and counterclockwise directions with respect to the reference direction. Therefore, for example, "45°" means ±45°.

[0011] A method for manufacturing a polarizing film according to one embodiment of the present invention includes a first step of bringing a resin film containing iodine and having a predetermined moisture content into contact with a first liquid, and may further include a second step of bringing the resin film into contact with a second liquid after the first step.

[0012] A. Method for Producing a Resin Film The resin film can be obtained, for example, by forming a resin layer (typically a polyvinyl alcohol-based resin layer) on a resin substrate to obtain a laminate or a resin film (typically a polyvinyl alcohol-based resin film), stretching and dyeing it with a dichroic substance (typically iodine), and then drying it. Hereinafter, the details of the method for producing the resin film will be described by taking the case of using a laminate as an example.

[0013] A-1. Laminate FIG. 1 is a schematic cross-sectional view showing the schematic configuration of a laminate according to one embodiment of the present invention. The laminate 1 has a thermoplastic resin substrate (for example, in a long shape) 2 and a polyvinyl alcohol (PVA)-based resin layer 3. Preferably, the laminate 1 is produced by forming a PVA-based resin layer 3 containing a PVA-based resin and a halide on the thermoplastic resin substrate 2. Specifically, a coating solution containing a PVA-based resin and a halide is applied on the thermoplastic resin substrate 2 and dried to form the PVA-based resin layer 3.

[0014] The thickness of the thermoplastic resin substrate is preferably 20 μm to 300 μm, more preferably 50 μm to 200 μm. If it is less than 20 μm, it may be difficult to form the PVA-based resin layer. If it exceeds 300 μm, for example, in the underwater stretching described later, the thermoplastic resin substrate may take time to absorb water and may require an excessive load for stretching.

[0015] The water absorption rate of the thermoplastic resin substrate is preferably 0.2% or higher, and more preferably 0.3% or higher. Such a thermoplastic resin substrate can absorb water, and the water acts as a plasticizer, causing plasticization. As a result, the tensile stress is significantly reduced, and it can be stretched to a high magnification. On the other hand, the water absorption rate of the thermoplastic resin substrate is preferably 3.0% or lower, and more preferably 1.0% or lower. With such a water absorption rate, it is possible to prevent problems such as a significant decrease in the dimensional stability of the thermoplastic resin substrate during manufacturing, which would lead to deterioration of the quality of the resulting polarizing film. It is also possible to prevent the thermoplastic resin substrate from breaking or the PVA-based resin layer from peeling off during underwater stretching. The water absorption rate of the thermoplastic resin substrate can be adjusted, for example, by introducing a modifying group into the constituent material. The water absorption rate is a value determined in accordance with JIS K 7209.

[0016] The glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 120°C or lower. By using such a thermoplastic resin substrate, it is possible to sufficiently ensure the stretchability of the laminate while suppressing the crystallization of the PVA-based resin layer. Furthermore, considering the plasticization of the thermoplastic resin substrate by water and the ability to perform underwater stretching well, the Tg is more preferably 100°C or lower, and even more preferably 90°C or lower. On the other hand, the Tg of the thermoplastic resin substrate is preferably 60°C or higher. With such a Tg, when applying and drying the coating liquid, it is possible to prevent defects such as deformation of the thermoplastic resin substrate (e.g., the occurrence of unevenness, sagging, wrinkles, etc.) and to produce a well-made laminate. In addition, the stretching of the resin layer can be performed well at a suitable temperature (e.g., around 60°C). The Tg of the thermoplastic resin substrate can be adjusted, for example, by introducing modifying groups into the constituent materials or by heating with a crystallizing material. The glass transition temperature (Tg) is a value determined in accordance with JIS K 7121.

[0017] Any suitable thermoplastic resin can be used as the constituent material of the thermoplastic resin substrate. Examples of thermoplastic resins include ester resins such as polyethylene terephthalate resins, cycloolefin resins such as norbornene resins, olefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. Among these, norbornene resins and amorphous polyethylene terephthalate resins are preferred.

[0018] In one embodiment, amorphous (non-crystallized) polyethylene terephthalate resin is preferably used. Among these, amorphous (less crystallized) polyethylene terephthalate resin is particularly preferred. Specific examples of amorphous polyethylene terephthalate resins include copolymers further containing isophthalic acid and / or cyclohexanedicarboxylic acid as the dicarboxylic acid, and copolymers further containing cyclohexanedimethanol or diethylene glycol as the glycol.

[0019] In another embodiment, a polyethylene terephthalate resin having isophthalic acid units is preferably used. This is because it has excellent stretchability and crystallization during stretching can be suppressed. This is thought to be due to the introduction of isophthalic acid units, which gives the main chain a large degree of bending. The polyethylene terephthalate resin has terephthalic acid units and ethylene glycol units. The content of isophthalic acid units is preferably 0.1 mol% or more, and more preferably 1.0 mol% or more, relative to the total of all repeating units. This is because a thermoplastic resin substrate with excellent stretchability can be obtained. On the other hand, the content of isophthalic acid units is preferably 20 mol% or less, and more preferably 10 mol% or less, relative to the total of all repeating units. This is because the degree of crystallinity can be increased well during drying, which will be described later.

[0020] The thermoplastic resin substrate may be stretched beforehand (for example, before forming the PVA resin layer). In one embodiment, the thermoplastic resin substrate is stretched transversely in a long shape. The transverse direction is preferably perpendicular to the stretching direction of the laminate described later. In this specification, "perpendicular" also includes substantially perpendicular directions. Here, "substantially perpendicular" includes the case where the direction is 90°±5.0°, preferably 90°±3.0°, and more preferably 90°±1.0°. The stretching temperature of the thermoplastic resin substrate is preferably Tg-10°C to Tg+50°C relative to the glass transition temperature (Tg) of the thermoplastic resin substrate. The stretching ratio of the thermoplastic resin substrate is preferably 1.5 to 3.0 times. Any suitable method can be used to stretch the thermoplastic resin substrate. Specifically, it may be fixed-end stretching or free-end stretching. The stretching method may be dry or wet. The stretching may be carried out in one stage or in multiple stages. If it is carried out in multiple stages, the stretching ratio is the product of the stretching ratios of each stage.

[0021] The above coating solution is typically a solution obtained by dissolving a PVA-based resin and a halide in a solvent. Examples of solvents include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, various glycols, polyhydric alcohols such as trimethylolpropane, and amines such as ethylenediamine and diethylenetriamine. These can be used alone or in combination of two or more. Among these, water is preferred. The content of the PVA-based resin in the coating solution is preferably 3 to 20 parts by weight per 100 parts by weight of the solvent. Within this range, a uniform coating film that adheres closely to the thermoplastic resin substrate can be formed. The content of the halide in the coating solution is preferably 5 to 20 parts by weight per 100 parts by weight of the PVA-based resin.

[0022] Examples of the above-mentioned PVA-based resins include polyvinyl alcohol and ethylene-vinyl alcohol copolymers. Polyvinyl alcohol is obtained by saponifying polyvinyl acetate. Ethylene-vinyl alcohol copolymers are obtained by saponifying ethylene-vinyl acetate copolymers. The degree of saponification of PVA-based resins is usually 85 mol% to 100 mol%, preferably 95.0 mol% to 99.95 mol%, and more preferably 99.0 mol% to 99.93 mol%. By using PVA-based resins with such a degree of saponification, a polarizing film with excellent durability can be obtained. If the degree of saponification is too high, there is a risk of gelation. The degree of saponification can be determined in accordance with JIS K 6726-1994.

[0023] The average degree of polymerization of PVA resins is typically 1000 to 10000, preferably 1200 to 4500, and more preferably 1500 to 4300. The average degree of polymerization can be determined in accordance with JIS K 6726-1994.

[0024] Any suitable halide can be used as the above-mentioned halide. For example, iodides such as potassium iodide, sodium iodide, and lithium iodide, and chlorides such as sodium chloride are examples. Among these, potassium iodide is preferred. By using a halide, a polarizing film with excellent optical properties can be obtained. Specifically, the crystallization of the PVA resin after the air-assisted stretching described later is promoted, and in subsequent wet processing (e.g., dyeing and water stretching described later), disorder in the orientation and decrease in orientation of polyvinyl alcohol molecules are suppressed, and a polarizing film with excellent optical properties can be obtained.

[0025] In preparing the coating solution, it is preferable to blend 5 to 20 parts by weight of halogen with 100 parts by weight of PVA resin, and more preferably 10 to 15 parts by weight. Specifically, the halogen content in the resulting PVA resin layer is preferably 5 to 20 parts by weight, and more preferably 10 to 15 parts by weight, per 100 parts by weight of PVA resin. If the amount of halogen relative to the PVA resin is too high, for example, the halogen may bleed out, and the resulting polarizing film may become cloudy.

[0026] Additives may be added to the coating solution. Examples of additives include plasticizers and surfactants. Examples of plasticizers include polyhydric alcohols such as ethylene glycol and glycerin. Examples of surfactants include nonionic surfactants. These are used, for example, to improve the uniformity, dyeability, and stretchability of the resulting PVA-based resin layer.

[0027] Examples of application methods for the above coating solution include roll coating, spin coating, wire bar coating, dip coating, die coating, curtain coating, spray coating, and knife coating (comma coating, etc.). The application and drying temperature of the coating solution is preferably 50°C or higher.

[0028] The thickness of the above PVA-based resin layer is preferably 3 μm to 40 μm, and more preferably 3 μm to 20 μm.

[0029] Before forming the PVA resin layer, the thermoplastic resin substrate may be subjected to surface treatment (e.g., corona treatment), or an easy-adhesion layer may be formed on the thermoplastic resin substrate. By performing such treatments, the adhesion between the thermoplastic resin substrate and the PVA resin layer can be improved.

[0030] A-2. Stretching The stretching described above is preferably carried out by dry stretching (air-assisted stretching) of the laminate followed by underwater stretching. Auxiliary stretching allows stretching while suppressing crystallization of the thermoplastic resin substrate, solving the problem of reduced stretchability due to excessive crystallization of the thermoplastic resin substrate in boric acid underwater stretching, and enabling stretching of the laminate to a higher magnification. Furthermore, when using a thermoplastic resin substrate, the coating temperature may be set low, which can lead to a problem where the crystallization of the PVA resin is relatively low and sufficient optical properties cannot be obtained. In contrast, by introducing auxiliary stretching, the crystallinity of the PVA resin can be increased even when using a thermoplastic resin. In addition, by increasing the orientation of the PVA resin in advance, problems such as a decrease in the orientation of the PVA resin or dissolution can be prevented during subsequent wet processing. In this way, a polarizing film with excellent optical properties can be obtained.

[0031] The method of aerial assisted stretching may be fixed-end stretching (for example, stretching using a tenter stretcher) or free-end stretching (for example, uniaxial stretching by passing the laminate between rolls with different peripheral speeds). Preferably, free-end stretching is employed. For example, heated roll stretching is employed, in which the laminate is stretched by the difference in peripheral speed between heated rolls while being conveyed in its longitudinal direction. In one embodiment, aerial assisted stretching includes a zone stretching step in a hot space (zone) and a heated roll stretching step. The order of the zone stretching step and the heated roll stretching step is not limited, but for example, the zone stretching step and the heated roll stretching step are performed in this order. In another embodiment, in a tenter stretcher, the film end is gripped and stretched by widening the distance between tenters in the flow direction (the widening of the distance between tenters becomes the stretching ratio). At this time, the distance of tenters in the width direction (perpendicular to the flow direction) is preferably set to be closer to the stretching ratio in the flow direction than that of free-end stretching. In the case of free-end stretching, the shrinkage rate in the width direction is given by the formula: Shrinkage rate in the width direction = (1 / stretching ratio) 1 / 2 It is calculated as follows.

[0032] The extension ratio for aerial assisted extension is preferably 2.0 to 3.5 times. Aerial assisted extension may be performed in one stage or in multiple stages. When performed in multiple stages, the extension ratio is the product of the extension ratios of each stage. The extension direction in aerial assisted extension is preferably substantially the same as the extension direction of underwater extension described later.

[0033] The stretching temperature in air-assisted stretching is set to an arbitrary appropriate value depending on the thermoplastic resin substrate used, the stretching method, etc. Preferably, the stretching temperature is above the glass transition temperature (Tg) of the thermoplastic resin substrate, more preferably above Tg+10°C, and even more preferably above Tg+15°C. On the other hand, the upper limit of the stretching temperature is preferably 170°C. By stretching at such a temperature, it is possible to suppress the rapid crystallization of the PVA-based resin and suppress problems caused by such crystallization (for example, hindering the orientation of the PVA-based resin layer by stretching).

[0034] The above underwater stretching is typically performed by immersing the laminate in a stretching bath. Underwater stretching allows stretching at a temperature lower than the glass transition temperature (typically around 80°C) of the thermoplastic resin substrate or PVA-based resin layer, enabling high-magnification stretching of the PVA-based resin layer while suppressing its crystallization. As a result, a polarizing film with excellent optical properties can be obtained.

[0035] The method of underwater stretching may be fixed-end stretching or free-end stretching (for example, uniaxial stretching by passing the laminate between rolls with different peripheral speeds). Preferably, free-end stretching is used. The stretching of the laminate may be carried out in one stage or in multiple stages. In the case of multiple stages, the stretching ratio of the laminate, as described later, is the product of the stretching ratios of each stage.

[0036] Stretching in water is preferably carried out by immersing the laminate in an aqueous boric acid solution (boric acid water stretching). By using an aqueous boric acid solution as the stretching bath, the PVA resin layer can be given rigidity to withstand the tension applied during stretching and water resistance that prevents it from dissolving in water. Specifically, boric acid can generate tetrahydroxyborate anions in the aqueous solution and crosslink with the PVA resin by hydrogen bonding. As a result, the PVA resin layer can be given rigidity and water resistance, allowing for good stretching and the acquisition of a polarizing film with excellent optical properties.

[0037] The above-mentioned aqueous boric acid solution is preferably obtained by dissolving boric acid and / or a borate in water, which is the solvent. The boric acid concentration is preferably 1 to 10 parts by weight, more preferably 2.5 to 6 parts by weight, and even more preferably 3 to 5 parts by weight, per 100 parts by weight of water. By setting the boric acid concentration to 1 part by weight or more, the dissolution of the PVA resin layer can be effectively suppressed, and a polarizing film with higher properties can be produced. In addition to boric acid or a borate, aqueous solutions obtained by dissolving boron compounds such as borax, glyoxal, glutaraldehyde, etc., in a solvent can also be used.

[0038] Preferably, an iodide is added to the stretching bath (boric acid aqueous solution). By adding an iodide, the elution of iodine adsorbed on the PVA resin layer can be suppressed. Examples of iodides include potassium iodide, lithium iodide, sodium iodide, zinc iodide, aluminum iodide, lead iodide, copper iodide, barium iodide, calcium iodide, tin iodide, and titanium iodide. The concentration of the iodide is preferably 0.05 to 15 parts by weight, and more preferably 0.5 to 8 parts by weight, per 100 parts by weight of water.

[0039] The stretching temperature (liquid temperature of the stretching bath) is preferably 40°C or higher, and more preferably 60°C or higher. At such temperatures, high-magnification stretching is possible while suppressing the dissolution of the PVA-based resin layer. Specifically, as described above, the glass transition temperature (Tg) of the thermoplastic resin substrate is preferably 60°C or higher in relation to the formation of the PVA-based resin layer. In this case, if the stretching temperature is below 40°C, even considering the plasticization of the thermoplastic resin substrate by water, good stretching may not be possible. On the other hand, the stretching temperature is, for example, 70°C or lower, preferably 67°C or lower, and more preferably 65°C or lower. The higher the stretching temperature, the higher the solubility of the PVA-based resin layer, and there is a risk that excellent optical properties cannot be obtained. The immersion time of the laminate in the stretching bath is preferably 15 seconds to 5 minutes.

[0040] The stretching ratio by underwater stretching is preferably 1.5 times or more, and more preferably 3.0 times or more. The total stretching ratio of the laminate (stretching ratio combining air-assisted stretching and underwater stretching) is preferably 5.0 times or more, more preferably 5.5 times or more, and even more preferably 6.0 times or more, relative to the original length of the laminate. By achieving such high stretching ratios, it is possible to manufacture polarizing films with extremely excellent optical properties. Such high stretching ratios can be achieved by employing an underwater stretching method (boric acid underwater stretching).

[0041] A-3. Dyeing The above dyeing is typically performed by adsorbing iodine onto a PVA-based resin layer. Methods for iodine adsorption include, for example, immersing the PVA-based resin layer (laminated structure) in a dyeing solution containing iodine, coating the PVA-based resin layer with the dyeing solution, or spraying the dyeing solution onto the PVA-based resin layer. Preferably, the laminate is immersed in the dyeing solution (dyeing bath) because this allows for good adsorption of iodine.

[0042] The above-mentioned dyeing solution is preferably an iodine aqueous solution. The amount of iodine added is preferably 0.05 to 0.5 parts by weight per 100 parts by weight of water. To increase the solubility of iodine in water, it is preferable to add iodide to the iodine aqueous solution. Specific examples of iodide are as described above. Potassium iodide is preferably used. The amount of iodide added is preferably 0.1 to 10 parts by weight, and more preferably 0.3 to 5 parts by weight, per 100 parts by weight of water. The temperature of the dyeing solution during dyeing is preferably 20°C to 50°C to suppress the dissolution of the PVA resin. When immersing the PVA resin layer in the dyeing solution, the immersion time is preferably 5 seconds to 5 minutes, and more preferably 30 seconds to 90 seconds, to ensure the permeability of the PVA resin layer.

[0043] The dyeing conditions (concentration, liquid temperature, immersion time) can be set, for example, so that the resulting resin film has a single-layer transmittance of 42% or more and a polarization degree of 85% or more. As for such dyeing conditions, for example, it is preferable that the ratio of iodine to potassium iodide content in the iodine aqueous solution used as the dyeing solution is 1:5 to 1:20, and more preferably 1:5 to 1:10.

[0044] When dyeing is performed immediately after a treatment in which a laminate is immersed in a treatment bath containing boric acid (for example, the immobilization treatment described later), boric acid may mix into the dyeing bath, changing the boric acid concentration in the dyeing bath and potentially leading to unstable dyeing properties. To suppress such instability in dyeing properties, the boric acid concentration in the dyeing bath is adjusted to preferably 4 parts by weight or less, more preferably 2 parts by weight or less, per 100 parts by weight of water. On the other hand, the boric acid concentration in the dyeing bath is preferably 0.1 parts by weight or more, more preferably 0.2 parts by weight or more, and even more preferably 0.5 parts by weight or more, per 100 parts by weight of water. In one embodiment, dyeing is performed using a dyeing bath that contains boric acid beforehand. This configuration can reduce the rate of change in boric acid concentration when boric acid is mixed into the dyeing bath. The amount of boric acid to be added to the dyeing bath in advance (the amount of boric acid not derived from the above treatment bath) is preferably 0.1 to 2 parts by weight, and more preferably 0.5 to 1.5 parts by weight, per 100 parts by weight of water.

[0045] A-4. Other processing If necessary, an insolubilization treatment is performed after the above-mentioned aerial assisted stretching, but before underwater stretching and dyeing. The insolubilization treatment is typically performed by immersing the PVA-based resin layer in an aqueous boric acid solution. By applying the insolubilization treatment, water resistance can be imparted to the PVA-based resin layer, and a decrease in the orientation of PVA when immersed in water can be prevented. The concentration of the aqueous boric acid solution in the insolubilization treatment is preferably 1 to 4 parts by weight per 100 parts by weight of water. The temperature of the insolubilization treatment (temperature of the aqueous boric acid solution) is preferably 20°C to 50°C.

[0046] If necessary, a crosslinking treatment is performed after dyeing and before underwater stretching. Typically, the crosslinking treatment is carried out by immersing the PVA resin layer in an aqueous boric acid solution. By applying the crosslinking treatment, water resistance can be imparted to the PVA resin layer, and a decrease in the orientation of PVA can be prevented during subsequent underwater stretching. The concentration of the aqueous boric acid solution in the crosslinking treatment is preferably 1 to 5 parts by weight per 100 parts by weight of water. It is preferable to add iodide to the aqueous boric acid solution. By adding iodide, the elution of iodine adsorbed on the PVA resin layer can be suppressed. Specific examples of iodide are as described above. The amount of iodide to add is preferably 1 to 5 parts by weight per 100 parts by weight of water. The temperature of the crosslinking treatment (temperature of the aqueous boric acid solution) is preferably 20°C to 50°C.

[0047] Preferably, washing is performed after stretching in water and before drying, as described later. Washing is typically performed by immersing the PVA-based resin layer in an aqueous potassium iodide solution.

[0048] A-5.Drying The above drying can be carried out in any suitable manner and under any conditions. Specifically, it may be carried out by heating the entire zone (zone heating method) or by heating the conveying rolls (heated roll method). Preferably, the heated roll method is used, and more preferably, both methods are used. By using heated rolls, heat curling of the laminate can be efficiently suppressed, and a polarizing film of superior quality can be manufactured. Specifically, by drying the laminate while it is aligned with the heated rolls, the crystallization of the thermoplastic resin substrate can be efficiently promoted and the degree of crystallinity can be increased, and even at relatively low drying temperatures, the degree of crystallinity of the thermoplastic resin substrate can be increased well. As a result, the rigidity of the thermoplastic resin substrate increases, making it able to withstand the shrinkage of the PVA-based resin layer due to drying, and curling is suppressed. Furthermore, by using heated rolls, the laminate can be dried while being kept in a flat state, so not only curling but also wrinkles can be suppressed.

[0049] Drying can shrink the laminate in the width direction, improving its optical properties. This is because it effectively enhances the orientation of PVA and the PVA / iodine complex. The shrinkage rate in the width direction of the laminate due to drying is preferably 1% to 10%, more preferably 2% to 8%, and even more preferably 4% to 6%. By using heated rolls, the laminate can be continuously shrunk in the width direction while being transported, achieving high productivity.

[0050] Figure 2 is a schematic diagram showing an example of drying using heated rolls. In the illustrated example, the laminate 200 is dried while being transported by transport rolls R1 to R6 heated to a predetermined temperature and guide rolls G1 to G4. In the illustrated example, the transport rolls R1 to R6 are arranged to continuously heat the PVA resin layer surface and the thermoplastic resin substrate surface alternately, but for example, the transport rolls R1 to R6 may be arranged to continuously heat only one side of the laminate 200 (for example, the thermoplastic resin substrate surface).

[0051] Drying conditions can be controlled by adjusting the heating temperature of the conveying rolls (temperature of the heating rolls), the number of heating rolls, and the contact time with the heating rolls. The heating roll temperature is preferably 60°C to 120°C, more preferably 65°C to 100°C, and even more preferably 70°C to 80°C. Such temperatures can increase the crystallinity of the thermoplastic resin, suppress curling, and provide the laminate with extremely excellent durability. The heating roll temperature can be measured using a contact thermometer. In the illustrated example, six conveying rolls are provided, but there are no particular restrictions on the number of conveying rolls as long as there are multiples. Typically, 2 to 40 conveying rolls are provided, preferably 4 to 30. The contact time between the laminate and the heating rolls (total contact time) is preferably 1 second to 300 seconds, more preferably 1 to 20 seconds, and even more preferably 1 to 10 seconds.

[0052] The heating rolls may be installed inside a heating furnace (e.g., an oven) or in a normal production line (at room temperature). Preferably, they are installed inside a heating furnace equipped with a blowing mechanism. By using heating roll drying in combination with hot air drying, abrupt temperature changes between the heating rolls can be suppressed, and shrinkage in the width direction can be easily controlled. The temperature for hot air drying is preferably 30°C to 100°C. The hot air drying time is preferably 1 second to 300 seconds. The wind speed of the hot air is preferably about 10 m / s to 30 m / s. This wind speed is the wind speed inside the heating furnace and can be measured with a mini-vane type digital anemometer.

[0053] A-6. Resin film The moisture content of the resin film subjected to the first step described later is, for example, 15% by weight or less, preferably 12% by weight or less, more preferably 9% by weight or less, and even more preferably 6% by weight or less. On the other hand, the moisture content of the resin film is, for example, 3% by weight or more. The resin film after the above drying process can satisfy such moisture content.

[0054] The resin film subjected to the first step described later preferably exhibits absorption dichroism at a wavelength of 380 nm to 780 nm. The transmittance (Ts) of the resin film is, for example, 42% or more, preferably 44% or more. The higher the transmittance, the easier the streaks tend to be to see. On the other hand, the transmittance (Ts) of the resin film is, for example, 49% or less.

[0055] The degree of polarization (P) of the resin film subjected to the first step described later is, for example, 85% or more, preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more. On the other hand, the degree of polarization of the resin film is, for example, 99.996% or less.

[0056] The above single-element transmittance is typically the Y value obtained by measuring with an ultraviolet-visible spectrophotometer and correcting for luminous sensitivity. The above polarization degree is typically determined by the following formula based on the parallel transmittance Tp and orthogonal transmittance Tc, which are measured with an ultraviolet-visible spectrophotometer and corrected for luminous sensitivity. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100

[0057] The orientation of the resin film subjected to the first step described later (PVA orientation) is, for example, 0.20 or higher, preferably 0.25 or higher, and more preferably 0.30 or higher. On the other hand, the orientation of the resin film (PVA orientation) is, for example, 0.40 or lower.

[0058] The orientation described above can be obtained, for example, by measuring the spectrum of the resin film (polarizing film) using the ATR method with a Fourier transform infrared spectrometer (e.g., the "Frontier FT-IR" model from PerkinElmer), and calculating the orientation of PVA from the obtained spectral results. Specifically, the spectrum of the resin film (polarizing film) is measured at polarization incidence of 0° and 90°, and the 2940 cm⁻¹ originating from -OH is calculated. -1 and 3300cm -1 Peak intensity ratio a(I 2940 / I 3330 ) is calculated. Then, as the two-color ratio, the ratio b(a) of intensity ratio a (when the incident angle is 0°) and intensity ratio a (when the incident angle is 90°) is calculated. 0° / a 90° This can be obtained by calculating (1-b) and then calculating c = (1-b) / [(2b+1)×(-2)] as an index of orientation. Here, the higher the value of c, the higher the orientation of the PVA.

[0059] The thickness of the resin film subjected to the first step described later is, for example, 12 μm or less, preferably 8 μm or less, and may also be 6 μm or less. According to the first step described later, streaks can be effectively eliminated from resin films of such thickness. On the other hand, the thickness of the resin film is preferably 1 μm or more, more preferably 2 μm or more.

[0060] B-1.First step As described above, in the first step, the resin film is brought into contact with the first liquid. Preferably, the resin film is immersed in the first liquid. When immersing the resin film in the first liquid, one side of the resin film may be supported (protected) by any suitable support substrate. In one embodiment, the resin substrate is used as the support substrate. Specifically, the resin film is immersed in the first liquid without peeling the resin substrate from the resin film (in the laminated state). In another embodiment, the protective layer described later is used as the support substrate. For example, after laminating the protective layer on the resin film surface of the laminate, the resin substrate is peeled off from the resin film to create a laminate of the protective layer and the resin film, and this laminate is immersed in the first liquid. When immersing in the first liquid, the resin film may be in the form of a long strip or a single sheet.

[0061] By contacting the first liquid, a polarizing film with excellent appearance can be obtained. Specifically, contact with the first liquid reduces the orientation of the resin film (PVA orientation), allowing components originally contained in the resin film (e.g., borate ions, iodide ions) to enter and exit the resin film, potentially eliminating streaks formed on the resin film. The difference in the orientation of the resin film (PVA orientation) before and after contact with the first liquid is, for example, 0.05 to 0.2. The orientation of the resin film (PVA orientation) after contact with the first liquid is, for example, 0.10 to 0.30.

[0062] Contact with the first liquid can increase the transmittance (Ts) of the resin film. The difference in transmittance (Ts) of the resin film before and after contact with the first liquid is preferably 1.5% or more, more preferably 3% or more, and may be 5% or more, or 7% or more. On the other hand, the difference in transmittance (Ts) of the resin film before and after contact with the first liquid is preferably 10% or less. The transmittance (Ts) of the resin film after contact with the first liquid is, for example, 45% or more, preferably 47% or more. On the other hand, the transmittance (Ts) of the resin film after contact with the first liquid is preferably 55% or less.

[0063] Contact with the first liquid may decrease the degree of polarization (P) of the resin film. The difference in the degree of polarization (P) of the resin film before and after contact with the first liquid is, for example, 10% to 20%. The degree of polarization (P) of the resin film after contact with the first liquid is, for example, 65% to 97%.

[0064] The temperature of the first liquid when it is brought into contact with the resin film is, for example, 60°C or higher, but may also be 65°C or higher, 70°C or higher, or 75°C or higher. By using the first liquid at such a temperature, for example, the orientation of the resin film (the orientation of PVA) can be reduced. On the other hand, the temperature of the first liquid is, for example, 90°C or lower, preferably 85°C or lower.

[0065] The immersion time (contact time) in the first liquid is set according to, for example, the temperature of the first liquid, the thickness of the resin film, the concentration of the components contained in the first liquid, etc. The immersion time in the first liquid is, for example, 1 minute to 60 minutes, preferably 2 minutes to 30 minutes.

[0066] A boric acid aqueous solution is preferably used as the first solution. By using a boric acid aqueous solution, the orientation of the resin film (PVA orientation) can be effectively reduced. For example, even if the temperature of the first solution is high (e.g., 60°C or higher), the orientation of the PVA can be reduced (the PVA chains can be loosened) without dissolving the resin film in the first solution, and the PVA can be re-crosslinked and homogenized by the inflow and outflow of borate ions. The concentration of the boric acid aqueous solution is preferably 4% by weight or more, and may be 4% by weight or more. On the other hand, from the viewpoint of the solubility of boric acid, the concentration of the boric acid aqueous solution is, for example, 7% by weight or less.

[0067] The first solution preferably contains an iodide such as potassium iodide. The inclusion of an iodide can promote the inflow and outflow of components originally present in the resin film. The concentration of iodide in the first solution is preferably 2% by weight or more. On the other hand, the concentration of iodide in the first solution is preferably 10% by weight or less. Such concentrations prevent the dyeing of the resin film from taking precedence over the inflow and outflow of components originally present in the resin film.

[0068] B-2.Second process As described above, in the second step, the resin film is brought into contact with the second liquid. Typically, the resin film is immersed in the second liquid. Similar to the first step, when immersing the resin film in the second liquid, it is preferable that one side of the resin film is supported (protected) by any suitable support substrate. The details are as described above. By contacting the resin film with the second liquid, it can be cleaned (for example, by boric acid cleaning). Also, by contacting the resin film with the second liquid, the hue of the resulting polarizing film can be adjusted.

[0069] Contact with the second liquid may reduce the transmittance (Ts) of the resin film. In one embodiment, the treatment conditions with the second liquid are adjusted according to the desired optical properties (e.g., transmittance, degree of polarization) of the resulting polarizing film. The difference in transmittance (Ts) of the resin film before and after contact with the second liquid is, for example, 0.1% to 10%. The transmittance (Ts) of the resin film after contact with the second liquid corresponds to the transmittance (Ts) of the polarizing film described later.

[0070] Contact with the second liquid can increase the degree of polarization (P) of the resin film. The difference in the degree of polarization (P) of the resin film before and after contact with the second liquid is, for example, 0.1% to 20%. The degree of polarization (P) of the resin film after contact with the second liquid corresponds to the degree of polarization (P) of the polarizing film described later.

[0071] Contact with the second liquid can increase the orientation of the resin film (PVA orientation). The difference in the orientation of the resin film (PVA orientation) before and after contact with the second liquid is, for example, 0.01 to 0.10. The orientation of the resin film (PVA orientation) after contact with the second liquid is, for example, 0.15 to 0.35.

[0072] The temperature of the second liquid when it comes into contact with the resin film is typically set to room temperature, for example, between 15°C and 40°C. The immersion time (contact time) in the second liquid is, for example, between 1 second and 1 minute.

[0073] The second solution typically contains an aqueous solvent (preferably water). The second solution may also contain an iodide such as potassium iodide. Including an iodide can suppress the bluish tint of the resulting polarizing film. The concentration of iodide in the iodide second solution is, for example, 2% to 10% by weight.

[0074] B-3. ​​Other processes The resin film (polarizing film) obtained through the second step described above can be dried. The drying temperature is, for example, 30°C to 60°C. The drying time is, for example, 15 seconds to 3 minutes.

[0075] C. Polarizing film The polarizing film obtained by the manufacturing method according to the embodiment of the present invention may exhibit absorption dichroism at any wavelength between 380 nm and 780 nm. The transmittance (Ts) of the polarizing film is preferably 42% or higher, but may also be 44% or higher, or 46% or higher. Such transmittance can contribute to reducing the power consumption of the image display device on which it is mounted. The manufacturing method according to the embodiment of the present invention makes it possible to obtain a polarizing film that combines high transmittance with excellent appearance. On the other hand, the transmittance (Ts) of the polarizing film may be, for example, 55% or less, but may also be 50% or less, or 48% or less.

[0076] The degree of polarization (P) of the polarizing film is, for example, 70% or more, preferably 75% or more, and more preferably 85% or more. On the other hand, the degree of polarization of the polarizing film is, for example, 98% or less.

[0077] The orientation of the polarizing film (PVA orientation) is preferably 0.20 or higher, and more preferably 0.25 or higher. On the other hand, the orientation of the resin film (PVA orientation) is, for example, 0.35 or lower.

[0078] The thickness of the polarizing film is, for example, 12 μm or less, preferably 8 μm or less, and may also be 6 μm or less. On the other hand, the thickness of the polarizing film is preferably 1 μm or more, more preferably 2 μm or more.

[0079] D. Polarizing plate A polarizing plate according to one embodiment of the present invention comprises the polarizing film and a protective layer or phase difference layer disposed on at least one side of the polarizing film.

[0080] Figure 3 is a schematic cross-sectional view showing the general configuration of a polarizing plate according to one embodiment of the present invention. The polarizing plate (polarizing plate with phase difference layer) 100 includes a polarizing film 10 having a first main surface 10a and a second main surface 10b facing each other, a protective layer 20 disposed on the first main surface 10a side (e.g., the viewing side) of the polarizing film 10, and a phase difference layer 30 and an adhesive layer 40 disposed on the second main surface 10b side of the polarizing film 10. The phase difference layer 30 may be a single layer or may have a laminated structure in which two or more layers are stacked. A second protective layer may also be disposed between the polarizing film 10 and the phase difference layer 30.

[0081] Although not shown in the diagram, the polarizer may further have other functional layers. The types, characteristics, number, combinations, and arrangements of the functional layers that the polarizer may have can be appropriately set according to the purpose. For example, the polarizer may further have a conductive layer or an isotropic substrate with a conductive layer. A polarizer having a conductive layer or an isotropic substrate with a conductive layer (a polarizer with a phase difference layer) can be applied, for example, to a so-called inner touch panel type input display device in which a touch sensor is incorporated inside the image display panel. As another example, the polarizer may further have other phase difference layers. The optical properties (e.g., refractive index characteristics, in-plane phase difference, Nz coefficient, photoelastic coefficient), thickness, and arrangement of the other phase difference layers can be appropriately set according to the purpose. As a specific example, the viewing side of the polarizing film 10 may be provided with other phase difference layers (typically, a layer that provides (elliptic) circular polarization function, a layer that provides ultra-high phase difference) to improve visibility when viewed through polarizing sunglasses. Having such a layer enables excellent visibility even when viewing the display screen through polarizing lenses such as polarizing sunglasses. Therefore, the resulting polarizing plate (polarizing plate with phase difference layer) can be suitably applied to image display devices that may be used outdoors.

[0082] Each component constituting the polarizing plate can be laminated via any suitable adhesive layer (not shown). Specific examples of adhesive layers include adhesive layers and tack layers. Specifically, the phase difference layer 30 may be bonded to the polarizing film 10 or the second protective layer via an adhesive layer (preferably using an active energy ray curable adhesive), or it may be bonded to the polarizing film 10 or the second protective layer via a tack layer. If the phase difference layer 30 has a laminated structure of two or more layers, each phase difference layer is bonded, for example, via an adhesive layer (preferably using an active energy ray curable adhesive).

[0083] Although not shown in the diagram, a release liner is practically bonded to the surface of the adhesive layer 40. The release liner can be temporarily attached until the polarizing plate is ready for use. By using the release liner, for example, the adhesive layer 40 is protected and the polarizing plate can be rolled.

[0084] The polarizing plate may be elongated or in sheet form. In this specification, "elongated" means an elongated shape in which the length is sufficiently longer than the width, for example, an elongated shape in which the length is 10 times or more, preferably 20 times or more, than the width. The elongated polarizing plate can be wound into a roll.

[0085] D-1.Protective layer The protective layer described above can be formed from any suitable film that can be used as a protective layer for the polarizing film. Specific examples of materials that make up the main component of the film include cellulosic resins such as triacetylcellulose (TAC), and transparent resins such as polyester, polyvinyl alcohol, polycarbonate, polyamide, polyimide, polyethersulfone, polysulfone, polystyrene, cycloolefins such as polynorbornene, polyolefins, (meth)acrylics, and acetates.

[0086] The above polarizing plate is typically disposed on the viewing side of an image display device. Therefore, the protective layer 20 may be subjected to surface treatments such as hard coat (HC) treatment, antireflection treatment, anti-sticking treatment, antiglare treatment, etc., as necessary.

[0087] The thickness of the protective layer is preferably 5 μm to 80 μm, more preferably 10 μm to 40 μm, and even more preferably 10 μm to 30 μm. When the above surface treatment is performed, the thickness of the protective layer is the thickness including the thickness of the surface treatment layer.

[0088] The second protective layer disposed between the polarizing film 10 and the retardation layer 30 is preferably optically isotropic in one embodiment. As used herein, "optically isotropic" means that the in-plane retardation Re(550) is 0 nm to 10 nm and the retardation in the thickness direction Rth(550) is -10 nm to +10 nm.

[0089] In one embodiment, the above resin substrate can be used as it is as the protective layer of the polarizing film. According to such a form, the manufacturing process can be reduced.

[0090] D-2. Retardation layer The retardation layer 30 may be a single layer or may have a laminated structure (for example, a two-layer structure) as described above.

[0091] The retardation layer 30 can have any appropriate optical properties according to applications and the like. In one embodiment, the retardation layer 30 includes a first retardation layer that can function as a λ / 4 plate. The first retardation layer typically exhibits a refractive index characteristic of nx > ny = nz. The in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 19 nm, more preferably nm to 170 nm, and even more preferably 120 nm to 160 nm. Here, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within the range not impairing the effects of the present invention, ny > nz or ny < nz may occur.

[0092] The Nz coefficient of the first phase difference layer described above is preferably 0.9 to 1.5, and more preferably 0.9 to 1.3. The first phase difference layer may exhibit inverse dispersion wavelength characteristics in which the phase difference value increases with the wavelength of the measured light. In this case, the Re(450) / Re(550) of the phase difference layer is preferably 0.8 or more and less than 1, and more preferably 0.8 or more and 0.95 or less.

[0093] The phase difference layer 30 can be composed of any suitable material, as long as it satisfies the desired properties. Specifically, the phase difference layer may be a resin film (stretched film), an oriented solidified layer of a liquid crystal compound, or a combination thereof.

[0094] D-3.Adhesive layer Any suitable configuration can be used for the adhesive layer 40. Specific examples include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and blending ratio of monomers forming the base resin of the adhesive, as well as the amount of crosslinking agent, reaction temperature, reaction time, etc., an adhesive with desired properties for a specific purpose can be prepared. The base resin of the adhesive may be used alone or in combination of two or more types. The base resin is preferably an acrylic resin (specifically, the adhesive layer is preferably composed of an acrylic adhesive). The thickness of the adhesive layer 40 is, for example, 10 μm to 20 μm.

[0095] D-4. Fabrication of polarizing plates A polarizing plate can typically be obtained by laminating various layers, such as a phase difference layer, onto a polarizing film obtained through the first and second steps described above. [Examples]

[0096] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these examples. The thickness and moisture content of the resin film are values ​​measured by the measurement methods described below. Unless otherwise specified, "parts" and "%" in the examples and comparative examples are based on weight. 1. Thickness Thicknesses of 10 μm or less were measured using a scanning electron microscope (JEOL Ltd., product name "JSM-7100F"). Thicknesses exceeding 10 μm were measured using a digital micrometer (Anritsu Corporation, product name "KC-351C"). 2. Moisture content of the resin film The resin film alone (the resin film peeled off from the resin substrate) was dried at 120°C for 2 hours, and the amount of water contained in the resin film was determined by measuring the change in weight before and after drying, thereby calculating the moisture content.

[0097] [Example 1] (Fabrication of resin film) As the thermoplastic resin substrate, an amorphous isophthalic copolymer polyethylene terephthalate film (thickness: 100 μm) in a long length, with a water absorption rate of 0.75% and a Tg of approximately 75°C was used. One side of the resin substrate was subjected to corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "Gosephymer Z410") in a 9:1 ratio. A PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60°C to form a 13 μm thick PVA-based resin layer, thereby creating a laminate. The resulting laminate was uniaxially stretched 2.4 times in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds in an oven at 130°C (air-assisted stretching). Next, the laminate was immersed for 30 seconds in an insolubilization bath at a liquid temperature of 40°C (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) (insolubilization treatment). Next, the resin film was immersed for 60 seconds in a staining bath at a liquid temperature of 30°C (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) while adjusting the concentration so that the individual permeability (Ts) of the resulting resin film was 43% or higher (staining). Next, the material was immersed for 30 seconds in a crosslinking bath at a liquid temperature of 40°C (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with 100 parts by weight of water) (crosslinking treatment). Subsequently, the laminate was immersed in a boric acid aqueous solution (boric acid concentration 4.0 wt%) at a liquid temperature of 64°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to achieve a total stretch ratio of 5.5 times (underwater stretching). Subsequently, the laminate was immersed in a washing bath at a liquid temperature of 20°C (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) (washing). Subsequently, the laminate was dried in an oven maintained at 90°C while being brought into contact with a SUS (stainless steel) heated roll with a surface temperature maintained at 75°C for approximately 2 seconds (drying). The shrinkage rate in the width direction of the laminate due to the drying shrinkage treatment was 5.2%. In this way, a resin film with a thickness of 5.5 μm and a moisture content of 4.4% was formed on the resin substrate.

[0098] Next, a 27 μm thick HC-cycloolefin resin (COP) film was bonded to one side of the obtained resin film (the side without the resin substrate) via an ultraviolet-curing adhesive. After that, the resin substrate was peeled off from the resin film to obtain a laminate of the HC-COP film and the resin film. The HC-COP film is a film in which an HC layer (2 μm thick) is formed on a cycloolefin resin (COP) film (25 μm thick), and it was bonded so that the COP film was on the side facing the resin film. The resulting laminate was immersed in a first solution (aqueous solution) with a boric acid concentration of 4% and a potassium iodide concentration of 10% at 70°C for 45 minutes. Then, it was immersed in a second solution (aqueous solution) with a concentration of 2% potassium iodide at room temperature for 15 seconds, and then dried at 60°C for 1 minute to obtain a polarizing plate having an HC-COP film and a polarizing film.

[0099] [Example 2] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that an aqueous solution with a boric acid concentration of 4% and a potassium iodide concentration of 5% was used as the first solution at 70°C, the immersion time in the first solution was set to 40 minutes, and water was used as the second solution.

[0100] [Example 3] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that an aqueous solution with a boric acid concentration of 4% and a potassium iodide concentration of 2% was used as the first solution at 66°C, the immersion time in the first solution was 30 minutes, and water was used as the second solution.

[0101] [Example 4] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that an aqueous solution with a boric acid concentration of 4% and a potassium iodide concentration of 2% was used as the first solution at 66°C, the immersion time in the first solution was 45 minutes, and water was used as the second solution.

[0102] [Example 5] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that an aqueous solution with a boric acid concentration of 4% and a potassium iodide concentration of 2% was used as the first solution at 60°C, the immersion time in the first solution was set to 40 minutes, and water was used as the second solution.

[0103] [Example 6] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that an aqueous solution with a boric acid concentration of 6% and a potassium iodide concentration of 10% was used as the first solution at 80°C, and the immersion time in the first solution was set to 20 minutes.

[0104] [Example 7] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that an aqueous solution with a boric acid concentration of 6% and a potassium iodide concentration of 5% was used as the first solution at 80°C, and the immersion time in the first solution was 20 minutes.

[0105] [Example 8] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that an aqueous solution with a boric acid concentration of 6% and a potassium iodide concentration of 2% was used as the first solution at 80°C, and the immersion time in the first solution was 20 minutes.

[0106] [Comparative Example 1] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that the treatment using the first and second liquids was not performed.

[0107] [Comparative Example 2] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that water at 50°C was used as the first liquid, the immersion time in the first liquid was set to 10 minutes, and no treatment with the second liquid was performed.

[0108] [Comparative Example 3] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that a 2% boric acid aqueous solution (without potassium iodide) at 70°C was used as the first solution, and the immersion time in the first solution was set to 2 minutes.

[0109] [Comparative Example 4] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that a 5% boric acid aqueous solution (without potassium iodide) at 70°C was used as the first solution, and the immersion time in the first solution was set to 5 minutes.

[0110] [Comparative Example 5] A polarizing plate having an HC-COP film and a polarizing film was obtained in the same manner as in Example 1, except that an aqueous solution of boric acid with a concentration of 8% at 70°C (without potassium iodide) was used as the first solution, and the immersion time in the first solution was set to 15 minutes.

[0111] [Comparative Example 6] A polarizing plate having a HC-COP film and a polarizing film was obtained in the same manner as in Comparative Example 1, except that the dyeing conditions were adjusted.

[0112] The following evaluations were performed on the examples and comparative examples. The evaluation results are summarized in Table 1. <Evaluation> · Single transmittance and degree of polarization For the polarizing film (polarizing film / HC-COP film), the single transmittance Ts, parallel transmittance Tp, and orthogonal transmittance Tc measured using an ultraviolet-visible spectrophotometer (V-7100, manufactured by JASCO Corporation) were defined as the Ts, Tp, and Tc of the polarizing film, respectively. These Ts, Tp, and Tc are Y values measured according to the 2-degree field of view (C light source) of JIS Z8701 and subjected to visual sensitivity correction. From the obtained Tp and Tc, the degree of polarization P was determined by the following formula. Degree of polarization P (%) = {(Tp - Tc) / (Tp + Tc)} 1 / 2 × 100

[0113] · Hue (a and b) For the polarizing film (polarizing film / HC-COP film), the single hue was measured using an ultraviolet-visible spectrophotometer (V-7100, manufactured by JASCO Corporation).

[0114] · Appearance 1 An evaluation laminate was prepared using the obtained polarizing plate. Specifically, the following retardation layer was bonded to the polarizing film side of the polarizing plate via an acrylic adhesive layer (15 μm), and then a reflective sheet ("Celapill DMS-X42", manufactured by Toray Film Processing Co., Ltd.) was bonded to the retardation layer via an acrylic adhesive layer (15 μm) to obtain an evaluation laminate. The reflectance of the reflective sheet measured in the SCI mode using a spectrophotometer ("CM-2600d", manufactured by Konica Minolta) was 88%. The appearance (presence or absence of streaks) when the obtained evaluation laminate was viewed from the polarizing plate side was observed visually. (Evaluation criteria) Good: No streaks were confirmed Bad: Streaks were confirmed

[0115] (Fabrication of stretched film constituting the phase difference layer) Polymerization was carried out using a batch polymerization apparatus consisting of two vertical reactors equipped with stirring blades and reflux condensers controlled to 100°C. The mixture consisted of 29.60 parts by mass (0.046 mol) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane, 29.21 parts by mass (0.200 mol) of isosorbide (ISB), 42.28 parts by mass (0.139 mol) of spiroglycol (SPG), 63.77 parts by mass (0.298 mol) of diphenyl carbonate (DPC), and 1.19 × 10⁻¹⁶ calcium acetate monohydrate as a catalyst. -2 Part of mass (6.78×10 -5 A mol (mol) of polymer was added. After purging the reactor with reduced pressure using nitrogen, the reactor was heated with a heat transfer medium, and stirring was started when the internal temperature reached 100°C. Forty minutes after the start of heating, the internal temperature was raised to 220°C, and while controlling the pressure to maintain this temperature, the pressure was reduced to 13.3 kPa 90 minutes after reaching 220°C. The phenol vapor produced as a by-product of the polymerization reaction was directed to a reflux condenser at 100°C, and the monomer components contained in the phenol vapor were returned to the reactor. The uncondensed phenol vapor was directed to a condenser at 45°C and recovered. Nitrogen was introduced into the first reactor to restore the pressure to atmospheric pressure, and then the oligomerized reaction mixture in the first reactor was transferred to the second reactor. Next, heating and depressurization in the second reactor were started, and the internal temperature reached 240°C and the pressure 0.2 kPa in 50 minutes. Polymerization was then allowed to proceed until the predetermined stirring power was reached. Once the predetermined power level was reached, nitrogen was introduced into the reactor to restore pressure, and the resulting polyester carbonate resin was extruded into water. The strands were then cut to obtain pellets.

[0116] The obtained polyester carbonate resin (pellets) was vacuum-dried at 80°C for 5 hours. Then, a long resin film with a thickness of 135 μm was produced using a film-making apparatus equipped with a single-screw extruder (manufactured by Toshiba Machine Co., Ltd., cylinder setting temperature: 250°C), a T-die (width 200 mm, setting temperature: 250°C), a chill roll (setting temperature: 120~130°C), and a winding machine. The obtained long resin film was stretched in the width direction at a stretching temperature of 143°C and a stretching ratio of 2.8 times to obtain a stretched film with a thickness of 47 μm. The Re(550) of the obtained stretched film was 143 nm, the Re(450) / Re(550) was 0.86, and the Nz coefficient was 1.12.

[0117] A laminated film was obtained in which a phase difference layer was formed by laminating a film exhibiting refractive index characteristics of nz>nx=ny (manufactured by Dai Nippon Printing Co., Ltd., "MCP-N(100)", Rth(550):-135nm) to the stretched film obtained above via an ultraviolet-curable adhesive (thickness after curing: 1.0 μm).

[0118] • Exterior 2 With the LED backlight (Altek, luminance measured at 7200 cd at a height of 50 cm with a measurement angle of 1.0 deg using Topcon Techno House's "SR-UL1R") turned on, the first polarizing plate (Nitto, "SEG1224DUHC", transmittance 43%), the resulting polarizing plate, and the second polarizing plate (Nitto, "SEG1224DUHC", transmittance 43%) were placed on top of it in that order, and the appearance (presence or absence of streaks) as viewed from above the second polarizing plate was observed visually. The three polarizing plates were arranged so that the absorption axis directions of adjacent polarizing plates were perpendicular (three-plate cross method). In addition, the first and second polarizing plates were placed in a state where they were bonded to a glass plate. (Evaluation Criteria) Good: No streaks were observed. Defect: A streak is visible.

[0119] [Table 1]

[0120] In the comparative example, streaks were visible along the absorption axis (stretching direction) of the polarizing film, but no streaks were visible in the example. In Comparative Example 2, which used the first solution without boric acid, it is thought that iodine was released from the areas with weaker crosslinking, making the streaks more visible. In Comparative Example 3, which used the first solution with less boric acid and a higher temperature, it is thought that the areas with weaker crosslinking dissolved, making the streaks more visible. [Industrial applicability]

[0121] The polarizing film according to the embodiment of the present invention is suitably used in image display devices such as liquid crystal displays, organic EL displays, and inorganic EL displays. [Explanation of Symbols]

[0122] 1. Laminate 2 Thermoplastic resin base material 3. Polyvinyl alcohol (PVA) resin layer 10 Polarizing film 20 protective layer 30 Retardation layer 40 Adhesive layer 100 polarizing plates

Claims

1. contacting a resin film containing iodine and having a moisture content of 15% by weight or less with a first liquid; The first liquid is an aqueous solution of boric acid and iodide, and the temperature of the first liquid is 60° C. or higher. A method for manufacturing a polarizing film.

2. The method according to claim 1 , wherein the resin film brought into contact with the first liquid has a single layer transmittance of 44% or more.

3. The method according to claim 1 , wherein the first liquid has a boric acid concentration of 4% by weight or more.

4. The method according to claim 1, wherein the iodide concentration in the first solution is 2% to 10% by weight.

5. The method according to claim 1 , further comprising contacting the resin film, which has been in contact with the first liquid, with a second liquid.

6. The method of claim 5 , wherein the second liquid comprises water.

7. The method according to claim 1 , which produces a polarizing film having a thickness of 8 μm or less.